Investigation of All-Solid-State batteries' Transition towards Large-Scale Processing with Emphasis on In Situ Gas Analysis - Teo, Jun Hao; Justus Liebig University Giessen (My University, 2022)
With liquid-based lithium-ion batteries approaching both its theoretical and practical limits, the progress in all-solid-state batteries (SSBs) offer an exciting improvement and future for energy storage systems. The exponential progress of SSBs on the laboratory/research-scale in the last decade has led to promising results and is currently on the cusp of large-scale implementation. The transition from lab-scale to industrial-scale is not trivial and require the considerations of several intertwined factors, for example safety, processability, performance, etc.…. In the present work, the use of industrial relevant materials are crucial for a seamless transition from liquid- to solid-based lithium ion batteries. The cathode active material (CAM) is a layered lithium transition metal oxides Li1+x(Ni1–y–zCoyMnz)1–xO2 (NCM or NMC). For the solid electrolyte (SE), sulfides (thiophosphate) are a popular choice largely due to both its processability and mechanical properties. The present work will address key questions on the safety aspect, specifically the gas evolution during cell operation using in situ gas analysis. Additionally, questions regarding the processability and performance will be addressed using a number of analysis techniques with in situ gas analysis in tandem. The first section will introduce the motivations and principles behind a lithium-ion battery and elaborate upon the active materials used for our study on SSBs. In the second section, the customized cell setup used for in situ gas analysis for SSBs will be elaborated. Additionally, we will provide an in-depth insight into the gassing technique used in this study (Differential electrochemical mass spectrometry, DEMS). The third section will elaborate upon the large-scale processing technique employed in our lab to produce sheet-based electrodes. The process of selection and optimization along every stage of the fabrication process will be described in detail. Lastly, in the fourth section (results and discussion), a compilation of the various publications can be found. The first publication will demonstrate the capabilities of the customized cell to investigate gas evolution in SSBs. This study was used to establish a baseline for future gassing studies on SSBs, thus the comparison between conventional liquid-based lithium-ion batteries (LIBs) and two sulfide-based SSBs (𝛽-Li3PS4 and Li6PS5Cl). The measurements first illustrate the differences in the type and amount of gas evolved between LIBs and SSBs, with LIBs mostly outgassing the SSBs except for two exceptions, namely O2 and SO2. The observation of toxic SO2 gas brings to attention the hazards of using sulfide SEs in SSBs. Additionally, the main contribution of CO2 gas evolution in SSBs was clarified to be a result of electrochemical decomposition of the coating (impurity) layer. This led to the further use of in situ gassing studies for the evaluation of coating chemistries in future publications. The second publication will display the transition toward large-scale processing techniques for SSBs. First, the individual processing steps (mixing, casting, drying) were optimized for the preparation of mechanically stable, homogeneous electrode sheets (section 3). The electrode sheets exhibited highly competitive performance versus those prepared using conventional powder-based processing. The second publication highlights a design-of-experiments (DoE)-guided approach to evaluate the influence of polymeric binder and carbon additives on the overall cell performance. The results were primarily supported by in situ gas analysis, which showed that certain polymeric functional group and/or chains/units potentially interact with the surrounding electrode components and lead to an increased degradation during cell operation. In the third publication, the dependence of cell performance on (chemo)mechanical effects was investigated. The combination of slurry-based processing and glassy SE was shown to improve the (chemo)mechanical properties of a cell, which allowed the cell components to maintain tight contact between each other while at the same time mitigating volume changes. The results demonstrate that the CAM/SE interface should not only function as a self-limiting interface, preventing further (electro)chemical reactions, but also possess the necessary mechanical strength needed to maintain intimate contact after prolonged cycling.
Untersuchung des Übergangs von Festkörperbatterien hin zur großtechnischen Verarbeitung mit Schwerpunkt in situ Gasanalyse
Keywords: NCM; In Situ Gas Analysis; DEMS; Slurry-based processing; All-Solid-State battery; ddc:500; ddc:540; ddc:600